High stress experienced in the foster and kin carer role: Understanding the complexities of the carer and child in context. (December 2018) - Harding, Leith; Murray, Kate; Shakespeare-Finch, Jane; Frey, Ron
Abstract: With the rising numbers of children in need of out-of-home care, child protection services look to foster and kin carers to play a leading role in the lives of children unable to live with their birth families. The current study examined placement, carer, and child characteristics related to perceived foster parent stress in a sample of 158 foster and kin carers in Queensland, Australia. Carers completed a self-report online survey that assessed parenting stress, and carer perceptions of the child in their care and the child protection system. Overall, foster carers reported high stress, with 20% in the clinical range on the Parenting Stress Index (PSI-4-SF). This stress was significantly higher for those providing care for children with carer-reported high emotional and behavioural problems. Both foster carer stress and the child's emotional and behavioural challenges were significantly related to placement factors, such as, the length of time the child had been in their current placement, and the child protection court order under which the child had been placed. The findings of the study highlight the challenges to caregivers in out-of-home care and the need for individualised services, resources and supports for caregivers under stress. Highlights: The perspective of foster and kin carers offers an avenue to understand the challenges of providing out-of-home care. The study explored foster parent's perception of stress and mental health in 158 Australian foster and kin carers. The carer's report of emotional and behavioural problems of the child was the strongest predictor of carer stress. Foster parent stress and the child's reported emotional and behavioral problems were related to the context of the placement.